Peningkatan Literasi Keuangan pada Remaja di Desa Sijeruk Kecamatan Banjarmangu Kabupaten Banjarnegara - Astohar Astohar; Aditya Yoga Prasetya; Rahmania Mustahidda; Rima Alifia (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
Teenagers today are filled with a number of rapid technological changes and developments. From a financial perspective, teenagers at this stage have a growing ability to understand the principles of saving and spending money, not only the basics, but also long-term goals. The three main areas that parents should focus on are income, savings, and responsible spending (shopping or investment). Problems that often occur in society (including teenagers) are such as wasteful living (lifestyle), online loan debt, and being trapped in online gambling. The emergence of several entertainment venues, cafes, and angkringan makes spending difficult for teenagers to control. The methods used in this service are lectures, simulations, discussions and questions and answers regarding the usefulness and benefits of understanding financial literacy. The results of this service show the different nature and patterns of financial management of teenagers requiring presentation patterns that need to be adjusted. In the implementation of the activity, there were participants (some) who were more enthusiastic or serious about this series of training. Presenters (speakers) require the application of andragogy model learning. This model is intended so that the presenter (material provider) and participants are not bored, comfortable in communicating and feedback appears quickly. In the future, training or workshops will be more directed to more technical or specific, for example capital market investment, mutual funds or other investment models.